PENGARUH PENAMBAHAN UBI UNGU (Ipomoea batatas l) TERHADAP KUALITAS SENSORIK, pH, DAN SINERESIS PADA PUDING SUSU KAMBING ETAWA: EFFECT OF ADDING PURPLE POTATO (Ipomoea batatas l) ON SENSORY QUALITY, pH, AND SYNERESIS IN ETAWA GOAT'S MILK PUDDING - Mutiara; Abdurrahman, Zakaria Husein; Prasetyo, Aris Budi (Universitas Boyolali, 2025)
This study aims to determine the effect of adding purple sweet potato concentration on the sensory quality of organoleptic tests and hedonic tests including (color, texture, taste, aroma, and aftertaste), pH value, and syneresis of Etawa goat milk pudding. The ingredients used are Etawa goat milk, purple sweet potato, white agar-agar powder, and sugar. In the first experiment (T0) without the addition of purple sweet potato, T1 the addition of 10% purple sweet potato, T3 the addition of 20% purple sweet potato and T3 the addition of 30% purple sweet potato. This study design used a Completely Randomized Design with treatments consisting of 4 treatments and 5 repetitions. Each repetition used the same ingredients and different ingredient compositions. Data obtained from the Organoleptic, Hedonic pH and Syneresis tests were analyzed using one-way ANOVA to find significant differences (P <0.01) that appeared between the average groups. The results of the study showed that the addition of purple sweet potato concentration had a very significant effect (P<0.01) on sensory quality (color, texture, taste, aroma, aftertaste) and pH value and did not have a very significant effect (P>0.01) on the syneresis of Etawa goat milk pudding. The addition of purple sweet potato affected the Sensory Quality of Etawa goat milk pudding. The addition of purple sweet potato had a very significant effect on organoleptic, Hedonic and pH tests, namely the addition of 30% purple sweet potato could improve the sensory quality of Etawa goat milk pudding to make it tastier and more preferred..